Musical Composition “Theme and Variations of the Sahur Arakan for Chamber Orchestra” - Zulpiana, Dila; Sidik, Hadaci; Murniati, Murniati; Zaidi, Ahmad (Institut Seni Indonesia Padangpanjang, 2023)
The composition of this music departs from the art of the tradition of Arakan Sahur. Tradition originating from the Kuala Tungkal area, Tungkal Ilir District, Tanjung Jabung Barat Regency, Jambi Province. Arakan Sahur is a tradition of waking people from sleeping in the month of Ramadan. This tradition is carried out when people eat at dawn. The composition of the Sahur Sahur Music is the music that is worked on in the form of music theme variations with the format of the chamber orchestra instrument. The goal is to get to get a dawn atmosphere with a different taste. The cultivation of the composition of the Sahur Sahur uses the technique of developing the main theme of the composition of the motifs, rhythm, and melody. Repetition of the main theme uses eight variations without eliminating the pattern of dawn.